Punkte: Für orchester - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2009)
Stockhausen conducts PUNKTE for orchestra ( Archive No. 37 / 1 )( Colour film by Suzanne Stephens )Dress rehearsal of PUNKTE for orchestra on February 5th 1993 with the symphony orchestraof the Hessen Radio, Frankfurt, conducted by Karlheinz Stockhausen )